2021
DOI: 10.3390/rs13061056
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Dust Storm in 2020 by a Multi-Observation Platform over the Northwest China

Abstract: Dust storms have occurred frequently in northwest China and can dramatically reduce visibility and exacerbate air quality in downwind regions through long-range transport. In order to study the distribution characteristics of dust particles sizes, structures and concentrations in the process of dust storm, especially for the vertical distributions, the multi-observation platform composed of six Lidars and nine aerosol analytical instruments is first used to detect a severe dust storm event, which occurred in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…This means that the height profiles of aerosol backscatter and extinction likely have nearly the same shape, one that follows the shape of the aerosol mass concentration (MC) profile. Thus, an opportunity is opened up for height profiling of the aerosol MC, using appropriate calibration [95], directly from the aerosol BSC profiles, without the need for intermediate determination of the aerosol extinction profiles. Here, this possibility is realized by using the vertical aerosol BSC profiles presented in Figures 9a,d,g and 10, together with data from parallel in situ measurements of the aerosol PM 10 concentration in the respective time intervals by the elevated rural Kopitoto AMS, shown in Figure 11a.…”
Section: Aerosol/dust Mass Concentration Profilingmentioning
confidence: 99%
“…This means that the height profiles of aerosol backscatter and extinction likely have nearly the same shape, one that follows the shape of the aerosol mass concentration (MC) profile. Thus, an opportunity is opened up for height profiling of the aerosol MC, using appropriate calibration [95], directly from the aerosol BSC profiles, without the need for intermediate determination of the aerosol extinction profiles. Here, this possibility is realized by using the vertical aerosol BSC profiles presented in Figures 9a,d,g and 10, together with data from parallel in situ measurements of the aerosol PM 10 concentration in the respective time intervals by the elevated rural Kopitoto AMS, shown in Figure 11a.…”
Section: Aerosol/dust Mass Concentration Profilingmentioning
confidence: 99%
“…Sandstorms are devastating natural hazards and one of the main global environmental problems which accelerate the expansion of desertification (Hu et al, 2017;Gu et al, 2021;Yang et al, 2021). Analyzing the temporal and spatial characteristics and the causes of sandstorms can help us better understand their occurrence and development, improving the level of sandstorm forecasting and reducing disaster impact and loss (Gasch et al, 2017;Li, 2020;Zhang and Zhou, 2020;Xu et al, 2020;Miri et al, 2021;Hamzeh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, wind, as a driving force, is the energy source of wind-blown sand movement. The structural characteristics of the flow field directly affect the surface sand emission and vertical transport (Zheng et al, 2013;Martin and Kok, 2017;Zhan et al, 2017). Wind velocity has been proven to have a more significant impact on sandstorms than other meteorological elements (Li, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the variation in horizontal dust flux with height, many researchers found that the transport flux declined sharply with increased height and proposed various distribution equations for dust flux versus height, which were primarily exponential functions [26][27][28][29][30] and power functions [31][32]. The latest research results of horizontal dust flux also include methods and verifications of empirical formulas with new data, and effects of weather and climate; experiments [33][34][35][36][37][38], such as the method of estimating low-frequency variations in the density of turbulent dust-aerosol fluxes over hyper-arid, arid, semi-arid and lake dried beds, have been proposed based on measurement data on aerosol-particle concentrations and the vertical wind velocity component [33]. Zhang et al [34] studied the distribution of biological soil crust in sand and dust storm source areas of Central and East Asia using moderate resolution imaging spectroradiometer satellite (MODIS) surface reflectance data collected in 2000-2019 to determine its potential impact on dust emission according to two empirical schemes.…”
Section: Introductionmentioning
confidence: 99%